2021
DOI: 10.32528/ijhs.v13i1.5150
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pelaksanaan Asuhan Keperawatan Keluarga terhadap Perawatan Kesehatan Anggota Keluarga Lansia

Abstract: Keluarga memiliki pengaruh yang penting tehadap pembentukan identitas individu, status kesehatan dan perasaan harga diri individu. Sistem pendukung yang vital bagi individu adalah keluarga, dimana keluarga berfungsi untuk memenuhi kebutuhan- kebutuhan anggota keluarga dengan menjalankan fungsi biologi, fungsi pendidikan, fungsi psikis, fungsi sosiokultural, serta fungsi kesehatan. Aktivitas-aktivitas keluarga dalam menjalankan fungsi kesehatan dan kesimbangan antara anggota keluarga tidak terlepas dari lima tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Of the 66 respondents, it was found that only 35 respondents (53%) had family with a good role as caregivers. 11 respondents (1.5%) have families with a poor role, and 30 respondents (45.5%) have families with a fairly good role (13,14).Older adults may face significant challenges in accessing TB services, which can be attributed to a variety of socioeconomic factors and health system challenges. One factor includes the lack of a comprehensive support system to help manage the complex health issues that disproportionately affect this population, as well as the physical and financial barriers that impede health care in older adults.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 66 respondents, it was found that only 35 respondents (53%) had family with a good role as caregivers. 11 respondents (1.5%) have families with a poor role, and 30 respondents (45.5%) have families with a fairly good role (13,14).Older adults may face significant challenges in accessing TB services, which can be attributed to a variety of socioeconomic factors and health system challenges. One factor includes the lack of a comprehensive support system to help manage the complex health issues that disproportionately affect this population, as well as the physical and financial barriers that impede health care in older adults.…”
Section: Resultsmentioning
confidence: 99%
“…This is because family nursing care is a series of activities to transfer knowledge and the family's ability to overcome existing health problems by using various strategies to improve behavior. The techniques or methods used include health education using verbal, psychomotor (practice), and affective to see the extent of family compliance in carrying out activities to overcome health problems in the family [7], [8].…”
Section: Discussionmentioning
confidence: 99%
“…This research method uses a pre-experimental one-group pre-post-test design [8], [9] The population in this study was 218 elderly people. The sampling technique used was purposive sampling, using predetermined inclusion criteria so that the number of samples obtained was 158 elderly families [9].…”
Section: Methodsmentioning
confidence: 99%
“…Keluarga adalah panduan terbaik untuk membantu remaja menaiki tangga kehidupan. Cara seorang anak muda, khususnya seorang remaja, memandang kehidupan akan berpengaruh pada kehidupan mereka ( [6]. Hal ini biasa terjadi pada anak-anak, ketika perawatan untuk anak-anak keluarga seringkali mengabaikan anaknya daripada menghabiskan waktu dan perawatan yang dibutuhkan oleh anak.…”
Section: Pendahuluanunclassified